Organizational and Pedagogical Conditions and Structural and Functional Model of Forming the Corporate Culture of Future Officers of the Armed Forces of Ukraine Using Pedagogical Technologies - Volodymyr Seliuk (Pedagogical Discourse, 2024)
The article focuses on the relevance of using pedagogical technologies in the field of education, in particular in the educational process of higher military educational institutions through the prism of forming the corporate culture of future officers of the Armed Forces of Ukraine. In accordance with the set goal (identification and justification of the essence of organizational and pedagogical conditions and structural and functional model of forming the corporate culture of future officers of the Armed Forces of Ukraine), a conceptual analysis of the categories «organizational and pedagogical conditions», «structural and functional model» is carried out. The essence of the definition «organizational and pedagogical conditions of forming the corporate culture of future officers of the Armed Forces of Ukraine by means of pedagogical technologies» is generalized. A number of dissertation studies, monographic publications, publications in scientific professional publications of researchers on the problem of determining organizational and pedagogical conditions in the educational process of higher military educational institutions were analyzed, the most effective organizational and pedagogical conditions for improving the quality of forming the corporate culture of future officers of the Armed Forces of Ukraine by means of pedagogical technologies were identified. Based on the analysis of regulatory documents in the field of military education, it was proven that the content of organizational and pedagogical conditions for forming the corporate culture of future officers of the Armed Forces of Ukraine by means of pedagogical technologies requires substantiation and detailed analysis. In order to identify the most effective pedagogical conditions for forming the corporate culture of future officers of the Armed Forces of Ukraine, an expert survey was conducted. A structural and functional model of forming the corporate culture of future officers of the Armed Forces of Ukraine, which consists of five blocks, was developed and substantiated. The essence, structure and goals of each block were revealed. It is concluded that the implementation of a structural and functional model of forming the corporate culture of future officers of the Armed Forces of Ukraine by means of pedagogical technologies in compliance with organizational and pedagogical conditions will allow to improve the quality of forming the corporate culture of future officers of the Armed Forces of Ukraine by means of pedagogical technologies.